Oligouridylate Binding Protein 1b Plays an Integral Role in Plant Heat Stress Tolerance - Nguyen, Cam Chau; Nakaminami, Kentaro; Matsui, Akihiro; Kobayashi, Shuhei; Kurihara, Yukio; Toyooka, Kiminori; Tanaka, Maho; Seki, Motoaki (Frontiers in Plant Science, 2016)
Stress granules (SGs), which are formed in the plant cytoplasm under stress conditions, are transient dynamic sites (particles) for mRNA storage. SGs are actively involved in protecting mRNAs from degradation. Oligouridylate binding protein 1b (UBP1b) is a component of SGs. The formation of microscopically visible cytoplasmic foci, referred to as UBP1b SG, was induced by heat treatment in UBP1b-overexpressing Arabidopsis plants (UBP1b-ox). A detailed understanding of the function of UBP1b, however, is still not clear. UBP1b-ox plants displayed increased heat tolerance, relative to control plants, while ubp1b mutants were more sensitive to heat stress than control plants. Microarray analysis identified 117 genes whose expression was heat-inducible and higher in the UBP1b-ox plants. RNA decay analysis was performed using cordycepin, a transcriptional inhibitor. In order to determine if those genes serve as targets of UBP1b, the rate of RNA degradation of a DNAJ heat shock protein and a stress-associated protein (AtSAP3) in UBP1b-ox plants was slower than in control plants; indicating that the mRNAs of these genes were protected within the UBP1b SG granule. Collectively, these data demonstrate that UBP1b plays an integral role in heat stress tolerance in plants.